Crazy Hair Day - Saltzberg, Barney (New York : Scholastic, 2003)
Stanley is excited about Crazy Hair Day at his school, until he discovers that he has gotten the date wrong.
K
b
b
Keywords: Hair -- Fiction; Schools -- Fiction